Dopamine-loaded nanoparticle systems circumvent the blood–brain barrier restoring motor function in mouse model for Parkinson’s Disease - Victoria Monge-Fuentes (Nature Portfolio, 2021)
Abstract Parkinson's disease (PD) is a progressive and chronic neurodegenerative disease of the central nervous system. Early treatment for PD is efficient; however, long-term systemic medication commonly leads to deleterious side-effects. Strategies that enable more selective drug delivery to the brain using smaller dosages, while crossing the complex brain-blood barrier (BBB), are highly desirable to ensure treatment efficacy and decrease/avoid unwanted outcomes. Our goal was to design and test the neurotherapeutic potential of a forefront nanoparticle-based technology composed of albumin/PLGA nanosystems loaded with dopamine (ALNP-DA) in 6-OHDA PD mice model. ALNP-DA effectively crossed the BBB, replenishing dopamine at the nigrostriatal pathway, resulting in significant motor symptom improvement when compared to Lesioned and L-DOPA groups. Notably, ALNP-DA (20 mg/animal dose) additionally up-regulated and restored motor coordination, balance, and sensorimotor performance to non-lesioned (Sham) animal level. Overall, ALNPs represent an innovative, non-invasive nano-therapeutical strategy for PD, considering its efficacy to circumvent the BBB and ultimately deliver the drug of interest to the brain.